Pembuatan E-Learning sebagai Media Pembelajaran di SMK Muhammadiyah Halmahera Barat - Alfanugrah A. Hi Usman; Salkin Lutfi; Muhammad Fhadli (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
One form of development of Information Technology (IT) in the world of education is the change in the order of the learning process from the conventional direction towards learning that can be carried out without geographical boundaries or what is known as E-learning. E-learning offers a learning concept that does not know place and time, where students can access it anytime and anywhere. This Community Service (PKM) aims to provide an E-Learning information system that can be used by all levels of schools.. The learning process at West Halmahera Muhammadiyah Vocational School is still conventional and the assignment collection process only uses email and WhatsApp so the assignment collection process is less effective. With E-Learning, it is hoped that it can become a medium for teachers and students to carry out a better learning process. Data collection methods were carried out by interviews, observations and literature reviews of related research. In building the e-learning system, the programming language used is PHP and MySQL as the database. With the e-system method. Learning can foster intensity between teachers and students and make it easier to obtain learning materials anywhere and without space and time limitations